Multiethnic children's literature - Ramirez, Gonzalo; Ramirez, Jan L. (Albany, N.Y. : Delmar Publishers, 1994)
From the Back Cover: This unique, now reference book is your guide to books for children in grades K-8 that accurately depict contemporary minority groups in the U.S. Covering books for and about Mexican Americans, Puerto Ricans, Latinos, African Americans, Chinese Americans, Asian Americans, and various Native Americans, this complete resource guide features: a brief history of multiethnic children's literature; discussions of current issues relevant to each minority group; suggestions for specific titles for children in grades K-2, 3-5 and 6-8; eye-catching photographs of recommended children's books; discussions of specific literary elements contained in each book; professional resources to help you locate culturally accurate literature.
Preface -- Acknowledgments -- About the authors -- Dedication -- Why Multiethnic Children's Literature? An Overview: -- Definition -- America's racial and ethnic diversity -- Multicultural or multiethnic education -- Racial and ethnic diversity in children's literature -- Value of multiethnic children's literature -- History of multiethnic children's literature: -- Multiethnic children's literature: the 1940s to the mid-1970s -- Multiethnic children's literature: the 1970s to the present -- Melting-pot books: 1940 to the present -- Quantity of multiethnic children's literature -- Future implications for multiethnic children's literature -- Locating multiethnic children's literature: -- Professional resources -- Review journals -- References -- Guidelines For Selecting Multiethnic Literature: -- Literary elements -- Plot -- Characterization -- Setting -- Author's style -- Theme -- Point of view -- Further evaluation of multiethnic literature: -- Using a second language -- Other issues to consider -- Conclusion -- References -- Books For And About Mexican Americans, Puerto Ricans, And Other Latinos: -- Latino versus Hispanic -- Mexican American children's literature -- Puerto Rican children's literature -- Literature for and about other Latinos -- References -- African American Children's Literature: -- Contemporary settings -- African American traditions -- African Americans to remember -- References -- Books For And About Chinese Americans, Japanese Americans, And Other Asian Americans: -- Chinese American children's literature -- Books about Japanese Americans -- Books about other Asian Americans -- References -- Books For And About Various Native Americans: -- Images of Native Americans -- Demographic information -- Literature for or about Native Americans -- Historical settings -- Contemporary settings -- References -- Activities For Extending Children's Experiences With Multiethnic Literature: -- Latino children's literature -- African American children's literature -- Asian American children's literature -- Native American children's literature -- References -- Conclusions: -- America's racial and ethnic diversity -- Growing need for multiethnic children's literature -- Implications for the future -- References -- Appendix: Publishers and addresses -- Index.
Includes index.
Includes bibliographical references and index.
Keywords: Minorities -- United States -- Juvenile literature -- Bibliography; Hispanic Americans -- Juvenile literature -- Bibliography; African Americans -- Juvenile literature -- Bibliography; Asian Americans -- Juvenile literature -- Bibliography; Indians of North America -- Juvenile literature -- Bibliography; African Americans -- Bibliography -- Juvenile literature; Asian Americans -- Bibliography -- Juvenile literature; Hispanic Americans -- Bibliography -- Juvenile literature; Indians of North America -- Bibliography -- Juvenile literature; Minorities -- Bibliography -- Juvenile literature -- United States